# How do you simplify  sqrt75+sqrt48?

Aug 12, 2018

$9 \sqrt{3}$

#### Explanation:

$\sqrt{75} = \sqrt{25 \times 3} = \sqrt{25} \times \sqrt{3} = 5 \sqrt{3}$

$\sqrt{48} = \sqrt{16 \times 3} = \sqrt{16} \times \sqrt{3} = 4 \sqrt{3}$

$\sqrt{75} + \sqrt{48} = 5 \sqrt{3} + 4 \sqrt{3} = 9 \sqrt{3}$

Aug 12, 2018

$9 \sqrt{3}$

#### Explanation:

$\sqrt{75} + \sqrt{48}$

$\therefore = \sqrt{5 \cdot 5 \cdot 3} + \sqrt{2 \cdot 2 \cdot 2 \cdot 2 \cdot 3}$

$\therefore \sqrt{2} \cdot \sqrt{2} = 2$

$\therefore \sqrt{5} \cdot \sqrt{5} = 5$

$\therefore = 5 \sqrt{3} + 4 \sqrt{3}$

$\therefore = 9 \sqrt{3}$

Aug 12, 2018

$9 \sqrt{3}$

#### Explanation:

$\sqrt{75} + \sqrt{48}$

=$\sqrt{{5}^{2} \cdot 3} + \sqrt{{4}^{2} \cdot 3}$

=$5 \sqrt{3} + 4 \sqrt{3}$

=$9 \sqrt{3}$

Aug 12, 2018

$9 \sqrt{3}$

#### Explanation:

$\sqrt{75} + \sqrt{48}$

$\implies \sqrt{3} \cdot \sqrt{25} + \sqrt{3} \cdot \sqrt{16}$

$\implies \sqrt{3} \cdot \left(\sqrt{25} + \sqrt{16}\right)$

$\implies \sqrt{3} \cdot \left(\sqrt{{5}^{2}} + \sqrt{{4}^{2}}\right)$

$\implies \sqrt{3} \cdot \left(5 + 4\right)$

$\implies 9 \sqrt{3}$